Hungarian Monitoring, 24 February 1988 . [Magyar rádiófigyelő], 1988. február 24 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Withdrawal of short-range missiles from the GDR - Demonstrations in Azerbaijan - Perspectives in Poland - Background to the Balkan conference Domestic Affairs: - Grósz and Kádár meet Gromyko separately - Károly Grósz at the Journalists' Union - Péter Várkonyi in Indonesia - Further crime rises in Hungary - On the Film Festival again Economy: - Treasury bills issued to reduce budget deficit - Problems in shoe manufacture Külpolitika: - A rövid hatótávolságú rakéták kivonása az NDK-ból - Tüntetések Azerbajdzsánban - Lengyelországi kilátások - A balkáni konferencia háttere Belpolitika: - Grósz és Kádár külön-külön találkozik Gromikoval - Grósz Károly az Újságíró Szövetségben járt - Várkonyi Péter Indonéziában - Tovább nőtt a bűnözés Magyarországon - Ismét a filmszemléről Gazdaság: - Kincstárjegyet bocsátanak ki a költségvetési hiány csökkentésére - Cipőipari gondok